The impact of moral judgment on bystanders’ interpersonal trust: the mediating role of trustworthiness - Zhen Zhang; Zhen Zhang; Xia Cai; Weiwei Gao; Zengtong Zhang; Chunhui Qi (Frontiers in Psychology)
Interpersonal trust is the premise and foundation of encouraging cooperation in this age of rapid progress. The purpose of this study was to investigate how moral judgment affects bystanders’ interpersonal trust and its internal mechanisms when there are ethical transgressions. The moral judgment of the evaluators was divided into three categories—opposition, neutrality and approval—on the basis of the moral transgressions of the offenders. Three moral judgment circumstances were randomly assigned to 143 primary school pupils, and the assessors scored the children via trustworthiness and trust scales. According to the findings, interpersonal trust is significantly predicted by moral judgment. Compared with neutral judgment, opposing moral violations significantly improves bystanders’ interpersonal trust in the evaluator, whereas approving moral violations does not significantly predict interpersonal trust. Trustworthiness plays a mediating role in the influence of moral judgment on interpersonal trust. Compared with neutral judgment, trustworthiness mediates the influence of opposed judgment on interpersonal trust rather than the influence of approved judgment on interpersonal trust. The findings demonstrate that moral opposition to transgressions influences interpersonal trust either directly or indirectly through trustworthiness.